2016
DOI: 10.3346/jkms.2016.31.9.1413
|View full text |Cite
|
Sign up to set email alerts
|

Association between Growth Differentiation Factor 15 (GDF15) and Cardiovascular Risk in Patients with Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: We investigated an association between serum Growth Differentiation Factor 15 (GDF15) level and cardiovascular risk in patients with newly diagnosed type 2 diabetes mellitus (T2D). A total of 107 participants were screened for T2D and divided into a T2D group and a control group (without diabetes). We used the Framingham risk score (FRS) and the New Pooled Cohort Equation score to estimate the 10-year risk of atherosclerotic cardiovascular disease. Serum GDF15 levels were measured using an enzyme-linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
6
39
1
Order By: Relevance
“…Whether GDF-15 could be involved as the protector from atherosclerotic injury with similar molecular mechanisms as mentioned above is not sufficiently clear. Although some scientists reported that levels of GDF-15 in people with diabetes demonstrated the close positive association with traditional CV risk factors, such as LDL cholesterol, BMI, age, inflammatory activity, but not with TG [14,15]. The results of our study well correspond with these findings, and we yielded that GDF-15 could be a component of the endogenous vascular repair system that maintains vascular integrity and function.…”
Section: Discussionsupporting
confidence: 87%
“…Whether GDF-15 could be involved as the protector from atherosclerotic injury with similar molecular mechanisms as mentioned above is not sufficiently clear. Although some scientists reported that levels of GDF-15 in people with diabetes demonstrated the close positive association with traditional CV risk factors, such as LDL cholesterol, BMI, age, inflammatory activity, but not with TG [14,15]. The results of our study well correspond with these findings, and we yielded that GDF-15 could be a component of the endogenous vascular repair system that maintains vascular integrity and function.…”
Section: Discussionsupporting
confidence: 87%
“…Elevated FGF21 and GDF15 are associated with diabetes and glucose intolerance (18,19) but have been shown to reduce serum glucose and insulin levels (20). Elevated FGF21 can act non-cell autonomously to induce uncoupling protein 1 (UCP1) in brown adipose tissue (BAT), resulting in increased mitochondrial oxidation of lipids (21).…”
mentioning
confidence: 99%
“…As expected, circulating GDF15 levels have also been shown to help identify and predict cardiovascular disease risk in patients with diabetes [16,38,39]. In a study with newly diagnosed T2DM patients, Shin et al [16] used the Framingham risk score and the New Pooled Cohort Equation score to estimate the 10-year risk of atherosclerotic cardiovascular disease. After adjusting for traditional risk factors, GDF15 was significantly positively correlated with both the Framingham risk score and the New Pooled Cohort Equation score, indicating that the levels of GDF15 may be a useful predictive biomarker of cardiovascular risk in newly Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In diabetic patients, higher levels of lipids and chronic inflammation may directly damage the cardiovascular system [37]. As expected, circulating GDF15 levels have also been shown to help identify and predict cardiovascular disease risk in patients with diabetes [16,38,39]. In a study with newly diagnosed T2DM patients, Shin et al [16] used the Framingham risk score and the New Pooled Cohort Equation score to estimate the 10-year risk of atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation